Three-dimensional mapping of temporo-limbic regions and the lateral ventricles in schizophrenia: gender effects - Narr, Katherine L; Thompson, Paul M; Sharma, Tonmoy; Moussai, Jacob; Blanton, Rebecca; Anvar, Bardia; Edris, Ahmad; Krupp, Rebecca; Rayman, Janice; Khaledy, Mohammad; Toga, Arthur W (Biological psychiatry (1969), 2001)
Background: Local alterations in morphological parameters are poorly characterized in several brain regions widely implicated in schizophrenia neuropathology. Methods: Surface-based anatomical modeling was applied to magnetic resonance data to obtain three-dimensional (3D) average anatomical maps and measures of location, shape, asymmetry, and volume for the lateral ventricles, hippocampus, amygdala, and superior temporal gyrus in schizophrenic ( n = 25; 15 male) and normal subjects ( n = 28; 15 male) matched for demographic variables. For all regions, intra-group variability was visualized and group differences assessed statistically to discriminate local alterations in anatomy across sex and diagnosis. Results: Posterior hippocampal volumes, lengths, and widths were reduced in patients. The right amygdala showed volume increases in schizophrenia patients versus controls. Ventricular enlargements, pronounced in the left hemisphere, occurred in the superior and lateral dimensions in patients, and these effects interacted with gender. Superior horn anterior extremes, inferior horn volumes, and hippocampal asymmetries exhibited gender effects. Significant group differences were absent in superior temporal gyrus parameters. Finally, regional variability profiles differed across groups. Conclusions: Clear morphometric differences of the lateral ventricles, hippocampus, and amygdala indicate regional displacements and shape distortions in several functional systems in schizophrenia. Alterations in these structures as mapped in 3D may provide the foundation for establishing brain abnormalities not previously defined at such a local level.